Inflammasome Activation in Myeloid Malignancies—Friend or Foe? - Andina, Nicola; Bonadies, Nicolas; Allam, Ramanjaneyulu (Frontiers in Cell and Developmental Biology, 2022)
Myeloid malignancies including myelodysplastic syndromes, myeloproliferative neoplasms and acute myeloid leukemia are heterogeneous disorders originating from mutated hematopoietic stem and progenitor cells (HSPCs). Genetically, they are very heterogeneous and characterized by uncontrolled proliferation and/or blockage of differentiation of abnormal HSPCs. Recent studies suggest the involvement of inflammasome activation in disease initiation and clonal progression. Inflammasomes are cytosolic innate immune sensors that, upon activation, induce caspase-1 mediated processing of interleukin (IL) -1-cytokine members IL-1β and IL-18, as well as initiation of gasdermin D-dependent pyroptosis. Inflammasome activation leads to a pro-inflammatory microenvironment in the bone marrow, which drives proliferation and may induce clonal selection of mutated HSPCs. However, there are also contradictory data showing that inflammasome activation actually counteracts leukemogenesis. Overall, the beneficial or detrimental effect of inflammasome activation seems to be highly dependent on mutational, environmental and immunological contexts and an improved understanding is fundamental to advance specific therapeutic targeting strategies. This review summarizes current knowledge about this dichotomous effect of inflammasome activation in myeloid malignancies and provides further perspectives on therapeutic targeting.